A Case Study on the Non-price Factors and Consumer Behaviour for Pangasius (Pangasianodon hypophthalmus) (Valenciennes, 1840) Consumption in Pune City, India - Mugaonkar, P.; Kumar, N. R.; Shelar, Gauri; Polanco, J. F.; Ramsubramanian, V.; Biradar, R. S. (Fishery Technology, 2017)
The consumption and preferences of Pangasius andthe constraints in the same have been investigatedamong consumers in Pune city, Maharashtra, India.Though 85.83% of respondents were aware aboutthe Pangasius as new catfish available for consumption,only 38.33% of them consumed it. Consumersquoted â€˜oilinessâ€™ (high fat content) of Pangasius asthe prime reason for non-consumption. Only 37.5%of consumers were willing to try processedPangasius. The consumers of â€œlow incomeâ€ andâ€œhigh incomeâ€ group showed significant differencein their expenditure on Pangasius. â€œLow incomeâ€group consumers spent more on Pangasius comparedto â€œHigh incomeâ€ group. Consumption ofPangasius can be improved by improving its qualityand creating awareness on perceived health hazards.Different cooking methods or use of Pangasius asraw material for other products may solve theproblem of â€˜oilinessâ€™ and may become popularamong high income group consumers.